Optimalisasi Pengawasan Petugas Aviation Security terhadap Pagar Perimeter Guna Menjamin Keamanan Penerbangan di Bandar Udara Internasional Yogyakarta - Nurdiana, Putri; Suprapti (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Aviation security is the most prioritized aspect to ensure the safety of passengers, aircraft crew and all important assets owned by the airport. One of the vital components in the airportsecurity system is the perimeter fence, because this component functions as the first line ofdefense in preventing illegalaccess to sensitive areas of the airport. The focus of this study is to determine the weak points in the surveillance system currently used on the perimeter fence at Yogyakarta International Airport.Through the preparation ofthisthesis, the weaknesses found will be analyzed so that they can improve the quality of supervision and reduce the potential for security disturbances. This study uses a qualitative approach, with data collection methods that include observation, interviews, and documentation. This approach is carried out to obtain primary and secondary data related to the real conditions of the security system at the airport. The object observed include the use ofmodern technology such as surveillance camera system (CCTV) which area expected to be a solution in strengthening perimeter fence security. The findings ofthis study are expected to provide relevant input and suggestions for airport managers and authorities, in order to improve the effectiveness of supervision of the perimeter area it is also hoped that the implementation of improvements suggested in this study will be able to reduce the risk ofsecurity disturbances and provide good protection for airports and users of aviation services.